Analisis Penambahan Gula Jagung Terhadap Karakteristik dan Degradasi Plastik Biodegradable Air Pati Ubi Kayu (manihot utilissima) - Miftahul Jannah (Department of Physics – Universitas Negeri Padang UNP, 2014)
Currently of materials used to package food and drink one of them is plastic. Along times, needs of plastics is increasing in many areas of life. The other, the use of plastic as a packaging material dealing with environmental issues, which can not be explained naturally by microbes in the soil. This leads to the buildup of plastic wastes that causes pollution and damage to the environment and also has a negative effect on human life. To reduce such problems, find solutions to make environmentally friendly plastics are biodegradable and do not spread pollution, the biodegradable plastic. Plastic biodegradable this study with the addition of corn sugar, 1g, 3g, 5g, 7 g and 9 g. Tests were carried out to obtain the value of flexural strength and degradation of biodegradable plastic water cassava starch as follows: corn sugar obtained without the addition of flexural strength kg/m2 8.81 x 103, 6.76 x tensile strength 103 kg/m2, 29.26% degradation. On the addition of 1g flexural strength obtained 19.03 x 103 kg/m2, tensile strength is 4.26 x 103 kg/m2, 11.88% degradation. On the addition of 21:26 flexural strength obtained 3g x 103 kg/m2, tensile strength is 2.82 x 103 kg/m2, 10:10% degradation. On the addition of flexural strength obtained 5g 29.20 x 103 kg/m2, tensile strength x 103 kg/m2 9:49, 7:01% degradation. For additional flexural strength values ​​obtained 7g 32.61 x 103 kg/m2, 12:18 tensile strength x 103 kg/m2, 6:59% degradation. On the addition of flexural strength obtained 9g 35.94 x 103 kg/m2, 13:46 tensile strength x 103 kg/m2, 5:01% degradation. Biodegradable plastic addition of cassava starch corn sugar has a value of flexural strength and tensile strength is good but slow degradation. Keywords:BiodegradablePlastic, CornSugar, Mechanical PropertiesandDegradatio